Computation of object approach by a system of visual motion-sensitive neurons in the crab Neohelice - Oliva, Damian Ernesto (2014)
.Similar to most visual animals, crabs perform proper avoidance responses to objects directly approaching them. The monostratified lobula giant neurons of type 1 (MLG1) of crabs constitute an ensemble of 14–16 bilateral pairs of motion-detecting neurons projecting from the lobula (third optic neuropile) to the midbrain, with receptive fields that are distributed over the extensive visual field of the animal's eye. Considering the crab Neohelice (previously Chasmagnathus) granulata, here we describe the response of these neurons to looming stimuli that simulate objects approaching the animal on a collision course. We found that the peak firing time of MLG1 acts as an angular threshold detector signaling, with a delay of δ = 35 ms, the time at which an object reaches a fixed angular threshold of 49°. Using in vivo intracellular recordings, we detected the existence of excitatory and inhibitory synaptic currents that shape the neural response. Other functional features identified in the MLG1 neurons were phasic responses at the beginning of the approach, a relation between the stimulus angular velocity and the excitation delay, and a mapping between membrane potential and firing frequency. Using this information, we propose a biophysical model of the mechanisms that regulate the encoding of looming stimuli. Furthermore, we found that the parameter encoded by the MLG1 firing frequency during the approach is the stimulus angular velocity. The proposed model fits the experimental results and predicts the neural response to a qualitatively different stimulus. Based on these and previous results, we propose that the MLG1 neuron system acts as a directional coding system for collision avoidance.